Penerapan User Center Design Dalam Rancangan Aplikasi SIPOLI (Sistem Informasi Poliklinik) - Syifa Nur Rakhmah; Adam Maulana Putra; Fajri Khairullah; Galih Khrisna Rangga (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Polyclinic Information System is a file containing notes and documents about the patient's and doctor's identity, examinations, medication, actions, and other services that have been provided to outpatients. The information system for recording transactions and medical records at the Dwi Ananda Clinic is still carried out conventionally, namely by recording in a medical record book, so mistakes often occur and the process of searching for patient data takes a long time. This study aims to create a computerized medical record information system to facilitate the search for patient medical records. The method used in conducting this research is descriptive method, by combining data collection methods and systems development methods. The development of this information system uses the application of User Center Design, where researchers carry out a series of procedures such as surveys and interviews to complete the data needed in program development to suit the needs of the Dwi Ananda Clinic. As a result, a web-based polyclinic information system that can make it easier for officers and doctors to view patient forms that have been carried out, can save the scanned medical record forms before they are destroyed, and can display the scanned forms that have been uploaded to the information system. This information system requires patient data to see the list of visits for the last 2 years used to determine the medical record files to be entered into the application. The polyclinic Information System application can make it easier to make medical transactions and outpatient medical records quickly and relevantly. After the implementation of the program, the Polyclinic Information System at the Dwi Ananda Clinic can provide a more complete and faster transaction service without reducing the accuracy of the information generated.